2008
DOI: 10.1128/jb.01678-07
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Extension of Ferrochelatase Is Critical for Enzyme Activity and for Functioning of the Tetrapyrrole Pathway in Synechocystis Strain PCC 6803

Abstract: Heme and chlorophyll (Chl) share a common biosynthetic pathway up to the branch point where magnesium chelatase and ferrochelatase (FeCH) insert either magnesium for Chl biosynthesis or ferrous iron for heme biosynthesis. A distinctive feature of FeCHs in cyanobacteria is their C-terminal extension, which forms a putative transmembrane segment containing a Chl-binding motif. We analyzed the ⌬H324 strain of Synechocystis sp. strain PCC 6803, which contains a truncated FeCH enzyme lacking this C-terminal domain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 46 publications
2
46
1
Order By: Relevance
“…The better viability of the gun4 Ϫ cells under low light or microaerobic conditions may be explained by the increased accumulation of P IX in this mutant (Table 1) as P IX is known to cause photooxidative damage (27). Recently, a very similar phenotype has been observed in a Synechocystis 6803 mutant that also accumulated large quantities of P IX , resulting from a mutation in the ferrochelatase gene (28). However, at low light intensities under microaerobic conditions no further improvement in Chl accumulation was observed, with the gun4 mutant accumulating about 25% of the wild-type Chl content.…”
Section: Discussionmentioning
confidence: 80%
“…The better viability of the gun4 Ϫ cells under low light or microaerobic conditions may be explained by the increased accumulation of P IX in this mutant (Table 1) as P IX is known to cause photooxidative damage (27). Recently, a very similar phenotype has been observed in a Synechocystis 6803 mutant that also accumulated large quantities of P IX , resulting from a mutation in the ferrochelatase gene (28). However, at low light intensities under microaerobic conditions no further improvement in Chl accumulation was observed, with the gun4 mutant accumulating about 25% of the wild-type Chl content.…”
Section: Discussionmentioning
confidence: 80%
“…The sensitivity of Gun4-less mutants to light and changes in ALA synthesizing capacity led to a hypothesis that Gun4 binds excessive porphyrins, which serves as a signal to down-regulate ALA formation (19,20). Although this model can explain reduced ALA synthesis in Gun4 or MgCh mutants (40), it is not consistent with the massive accumulation of P IX in ferrochelatase mutants (8,41).…”
Section: Mechanism Of Porphyrin Binding To the Gun4 Protein-gun4mentioning
confidence: 72%
“…Although these data do not exclude the possibility that the amino acid modification exerted conformational changes on other parts of LIL3, we think this is unlikely because the experiments with LIL3(TM APX ) indicated that the conformation of the TM domain and that of the other part of LIL3 were independent from each other. In the case of cyanobacterial FC, removal of the LHC motif from the FC sequence resulted in the dissociation of the FC dimer into monomers (23). The results led us to hypothesize that the modification of the LHC motif in TM LIL3 also affects the oligomerization of LIL3-GGR complexes.…”
Section: Substitution Of the Lhc Motif With The Tm Apx Domain In The mentioning
confidence: 96%
“…At least three specific functions have been postulated for the LHC motif: membrane anchoring, providing binding sites of tetrapyrroles, and facilitating protein-protein interactions (5,22). The function of the LHC motif of cyanobacterial FC has been studied at both the in vivo and in vitro levels (22)(23)(24). Although removal of the LHC motif from the FC sequence did not affect its catalytic activity, it resulted in a dissociation of the dimeric FC into monomers (22) and in the increased turnover of the FC reaction (24).…”
mentioning
confidence: 99%